2007
DOI: 10.1111/j.1471-3802.2007.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

What is meant by ‘support’ in higher education? Towards a model of academic and welfare support

Abstract: This paper focuses on academic and welfare support for students in higher education, and specifically what makes that support effective. It draws on data from a research project which aimed to explore networks of support for disabled and non‐disabled students. Part of the research focused on the nature and sources of support that were identified as important by students, as well as the kinds of support that were available within the higher education institution (HEI). What emerged as of particular interest was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…As with other structures of inequality, enrolling more disabled students in HE does not automatically lead to full participation in university life or equality. While quantitative increases are important, access needs to be accompanied by support to attain and remain in the sector (Richardson & Wydell, 2003;Jacklin & Robinson, 2007;Matshedisho, 2007). Hence, there is the need to mainstream action to address disability into services, planning and resource allocation (Albert et al, 2005).…”
Section: Conceptualising Disability In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other structures of inequality, enrolling more disabled students in HE does not automatically lead to full participation in university life or equality. While quantitative increases are important, access needs to be accompanied by support to attain and remain in the sector (Richardson & Wydell, 2003;Jacklin & Robinson, 2007;Matshedisho, 2007). Hence, there is the need to mainstream action to address disability into services, planning and resource allocation (Albert et al, 2005).…”
Section: Conceptualising Disability In Higher Educationmentioning
confidence: 99%
“…Inclusive education is created by inclusive cultures as well as by policies (Booth et al, 2000). While Jacklin & Robinson's (2007) study in the United Kingdom found that disabled HE students valued the informal support offered by fellow students, friends and family, Chataika (2010) in Zimbabwe and Karangwa (2008) in Rwanda found that disabled students were often reliant on the informal support given by non-disabled peers, such as reading key texts aloud for blind students.…”
Section: Conceptualising Disability In Higher Educationmentioning
confidence: 99%
“…ISSN 2330-9709 2015 www.macrothink.org/jet 150 A further two studies (Deprez & Butler, 2007;Alsop, Gonzalez-Arnal & Kilkey, 2008) reported the role of financial support provided by the state and higher education institutions for low-income women and mature student-carers respectively. One (Jacklin & Robinson, 2007) explored disabled and non-disabled students' perceptions of support, the nature and sources of support, effects of support on the students' experience of higher education and the rest (Benseman, Coxon, Anderson & Anae, 2006;Padilla-Carmona, 2012) reported on students' experiences of higher education and the factors that contribute to or hinder their successful completion of HE.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Four of the studies had participants of mixed ages (Wilcox et al, 2005;Benseman et al, 2006;Jacklin & Robinson, 2007;Field & Morgan-Klein, 2012) and more conventional-aged students than adults. Three focused on adults aged 23 (Deprez & Butler, 2007) or 25 and above (Alsop et al, 2008;Padilla-Carmona, 2012) who had dependent children.…”
Section: Description Of Participantsmentioning
confidence: 99%
“…In terms of academic support students want help with their assessments around exam technique, essay writing and referencing as well as personal development planning and career advice (7,9,12,13,14). Procedural support is usually focused on negotiating University regulations and policies (11) and pastoral support covers a range of areas such as housing, finance, advice and help related to illness or personal issues and referral to others who can provide support (7,11,12). As a personal tutor the complexity of issues faced do lead to questions about how one person can provide appropriate support (15).…”
mentioning
confidence: 99%